2020
DOI: 10.1111/jdi.13443
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarker in serum for predicting susceptibility to type 2 diabetes mellitus: Free fatty acid 22:6

Abstract: Aims/Introduction: Type 2 diabetes mellitus is closely linked to increased levels of free fatty acids (FFAs) in obese individuals, although which FFA is most associated with type 2 diabetes mellitus is unclear. This study aimed to identify the specific FFAs that best predict the occurrence of type 2 diabetes mellitus in obese individuals, and assess their potential application value. Materials and Methods: Participants were divided into three groups: a normal weight group (n = 20), an obese group (n = 10) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Finally, in obese subjects, in addition to the altered pattern of adipokines secretion, AT releases greater quantities of FFAs [ 144 ], which are associated with insulin resistance and lipotoxicity [ 144 , 145 ]. In particular, while some studies report an increase in the levels of SFAs (i.e., palmitic acid [ 146 ], decanoic acid, and caprylic acid [ 147 ]), in obese subjects, unsaturated fatty acids levels have been found to be both decreased (i.e., oleic acid [ 147 ] and linoleic acid [ 146 , 148 ]) and increased (i.e., palmitoleic acid [ 146 , 149 ], dihomo-gamma-linolenic acid [ 149 ], and docosaesaenoic acid [ 147 ]).…”
Section: Dysfunctional Adipose Tissue In Obesity: Alteration Of the A...mentioning
confidence: 99%
“…Finally, in obese subjects, in addition to the altered pattern of adipokines secretion, AT releases greater quantities of FFAs [ 144 ], which are associated with insulin resistance and lipotoxicity [ 144 , 145 ]. In particular, while some studies report an increase in the levels of SFAs (i.e., palmitic acid [ 146 ], decanoic acid, and caprylic acid [ 147 ]), in obese subjects, unsaturated fatty acids levels have been found to be both decreased (i.e., oleic acid [ 147 ] and linoleic acid [ 146 , 148 ]) and increased (i.e., palmitoleic acid [ 146 , 149 ], dihomo-gamma-linolenic acid [ 149 ], and docosaesaenoic acid [ 147 ]).…”
Section: Dysfunctional Adipose Tissue In Obesity: Alteration Of the A...mentioning
confidence: 99%
“…It should be noted that some of biomarkers we found in this work, FFA (16:1), FFA (20:5), TAG (50:2), TAG (52:1), TAG (52:3), TAG (52:4), TAG (52:5), TAG (54:3), TAG (54:4), TAG (54:5), and TAG (56:6), also have shown changed distinctly in patients during the onset and progression of metabolic-associated diseases, such as MAFLD, 47 type 2 diabetes, 48 obesity, 8 and cardiovascular disease. 49 Nevertheless, these previous studies with traditional approaches found only a single indicator or a few indicators at a time.…”
Section: Sbp Alleviates Metabolic Disorders In Long-term Hfd-fed Mice...mentioning
confidence: 99%
“…Excess FFAs and hyperglycemia can lead to the impairment of beta‐cells by inducing endoplasmic reticulum (ER) stress through activation of the apoptotic unfolded response (UPR) pathways. The stress induced by excess saturated FFAs activates the UPR pathway, leading to inhibition of the sarco/ER Ca2+ ATPase (SERCA), activation of IP3 receptors, or direct damage of ER homeostasis 30 . Insulin resistance, marked by heightened glucose production in the liver and reduced glucose utilization in the liver, muscles, and adipose tissue, is a key player in T2DM.…”
Section: Pathophysiology Of Diabetesmentioning
confidence: 99%